LB1530. Clinical Benefit of Oral sabizabulin for Hospitalized Adults with CoVID-19 on Supplemental Oxygen. (15th December 2022) - Gonzales, Tara L; Skarda, Paula; Bird, Thomas G; Schnaus, Michael; Steiner, Mitchell; Skolnick, Alan; Gary Barnette, K; Gordon, Michael S; Sprinz, Eduardo; Rodriguez, Domingo; Rodriguez, Domingo; Kalaydzhiev, Petar; et al.
Abstract: Background: Sabizabulin is an oral, novel microtubule disruptor with dual antiviral and anti-inflammatory activities. A randomized, multicenter placebo-controlled Phase 3 clinical trial was conducted in hospitalized moderate-severe COVID-19 patients at high-risk for acute respiratory distress syndrome (ARDS) and death. Patients were randomized (2:1) to sabizabulin 9mg or placebo oral daily dose (up to 21 days). In a planned interim analysis, sabizabulin treatment resulted in a 55.2% relative reduction in mortality compared to placebo. Methods: The primary endpoint was all-cause mortality up to day 60. Key secondary endpoints were days in intensive care unit (ICU), on mechanical ventilation, and in hospital. Randomization was stratified by oxygen requirement at baseline (WHO 4 = supplemental oxygen, WHO 5 = NIV/forced oxygen, WHO 6 = mechanical ventilation). The WHO 4 patients also were required to have at least one comorbidity (Asthma, Chronic Lung Disease, Diabetes, Hypertension, Severe Obesity (BMI ≥40), ≥65 years of age, in a nursing/long-term care facility, or immunocompromised). A post-hoc analysis of the key efficacy outcomes in WHO 4 at baseline patients with a comorbidity was conducted. Results: A total of 88 patients classified as WHO 4 with a baseline comorbidity underwent randomization (59 sabizabulin/29 placebo). Baseline characteristics were similar. Sabizabulin treatment resulted in a 22.4 absolute percentage point and 81.2% relative reduction in deaths compared to the placebo (odds ratio 6.22, 95% CI [1.58 to 24.48], p=0.0090). Mortality rate was 5.2% (3 of 58) for sabizabulin versus 27.6% (8 of 29) for placebo. Key secondary endpoints: sabizabulin treatment resulted in relative reductions of 74.7% in days in ICU (p=0.0021), 80.7% in days on mechanical ventilation (p=0.0019), and 39.8% in days in hospital (p=0.0191) vs placebo. Conclusion: Statistically and clinically significant reductions in mortality, days in the ICU, on mechanical ventilation, and in the hospital were observed in the sabizabulin treated compared to placebo hospitalized COVID-19 WHO-4 patients with at least one comorbidity suggesting that the antiviral action of sabizabulin contributes early in the prevention of COVID-19 progression to ARDS and death. Disclosures: Tara L. Gonzales, MD, Veru Inc.: Employee Mitchell Steiner, MD, Veru, Inc: Board Member|Veru, Inc: Stocks/Bonds K. Gary Barnette, PhD, Veru Inc.: Employee|Veru Inc.: Ownership Interest Michael S. Gordon, MD, Agenus: Grant/Research Support|Arcus: Grant/Research Support|Astex: Grant/Research Support|ATEA: Grant/Research Support|Beigene: Grant/Research Support|Caremission: Ownership Interest|Celldex: Grant/Research Support|Corcept: Grant/Research Support|Daiichi: Grant/Research Support|Deciphera: Grant/Research Support|Endocyte: Grant/Research Support|Forma: Grant/Research Support|FujiFilm: Grant/Research Support|Genentech/Roche: Grant/Research Support|I-MAB Pharma: Grant/Research Support|Imaginab: Advisor/Consultant|Imaginab: Grant/Research Support|Imaging Endpoints: Advisor/Consultant|Incyte: Grant/Research Support|Kinevant: Grant/Research Support|Medelis: Ownership Interest|Medimmune: Grant/Research Support|Morphic Tx: Advisor/Consultant|Nikang: Grant/Research Support|OncoResponse: Grant/Research Support|OnQuality: Advisor/Consultant|Pfizer: Advisor/Consultant|Pfizer: Grant/Research Support|Pionyr: Grant/Research Support|Plexxicon: Grant/Research Support|Qualigen: Advisor/Consultant|RedHill Bio: Grant/Research Support|Revolution Medicine: Grant/Research Support|Riboscience: Grant/Research Support|Seattle Genetics: Grant/Research Support|Serono: Grant/Research Support|SQZ Biotech: Grant/Research Support|Syndax: Grant/Research Support|Theseus: Grant/Research Support|Tolero: Grant/Research Support|Tracon: Grant/Research Support|Vedanta: Grant/Research Support|Veru: Grant/Research Support Eduardo Sprinz, MD; MsC, ScD, Gilead: Advisor/Consultant|Gilead: Board Member|GSK: Advisor/Consultant|GSK: Board Member|GSK: Grant/Research Support|GSK: Honoraria|Janssen: Advisor/Consultant|Janssen: Board Member|Janssen: Honoraria Domingo Rodriguez, n/a, Veru: Stocks/Bonds Domingo Rodriguez, n/a, Veru: Stocks/Bonds.